2018
DOI: 10.14704/nq.2018.16.6.1628
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Effects of Sevoflurane and Propofol on Cerebral Oxygen Metabolism in Pediatric Anesthesia

Abstract: This paper aims to study the effect of sevoflurane and propofol on cerebral oxygen metabolism during the maintenance of paediatric anaesthesia. To this end, the children who had undergone surgical treatment in General Surgery Department were selected as study subjects, and they were divided into experimental group and control group. Patients in the control group received propofol to maintain anesthesia, while patients in the experimental group maintained anaesthesia with sevoflurane. Then, the hemodynamic chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Indeed, monitoring the supply and demand balance of cerebral oxygen during surgical anesthesia is helps protect the brain. [ 20 ] SjvO 2 and CERO 2 are the key indices for monitoring cerebral oxygen metabolism. [ 7 , 21 ] In the current study, the SjvO 2 value was shown to increase with the prolongation of anesthesia time after anesthesia induction.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, monitoring the supply and demand balance of cerebral oxygen during surgical anesthesia is helps protect the brain. [ 20 ] SjvO 2 and CERO 2 are the key indices for monitoring cerebral oxygen metabolism. [ 7 , 21 ] In the current study, the SjvO 2 value was shown to increase with the prolongation of anesthesia time after anesthesia induction.…”
Section: Discussionmentioning
confidence: 99%